Aflatoxins Occurrence, Detoxification, Determination and Health Risks - Bola Abdulra'uf, Lukman (IntechOpen, 2022)
Aflatoxins are a group of highly toxic and carcinogenic substances that occur naturally and can be found in food substances. Aflatoxins are secondary metabolites of certain strains of fungi Aspergillus flavus and Aspergillus parasiticus as well as the less common Aspergillus nomius. Aflatoxins B1, B2, G1, and G2 are the most important members, which can be categorized into two groups according to chemical structure. As a result of the adverse health effects of mycotoxins, their levels have been strictly regulated, especially in food and feed samples. Therefore, their accurate identification and determination remain a herculean task due to their presence in the complex food matrix. The great public concern and the strict legislation incited the development of sensitive analytical methods that are discussed in this book.